2020
DOI: 10.1016/j.bcp.2020.114103
|View full text |Cite
|
Sign up to set email alerts
|

Combined anti-fibrotic and anti-inflammatory properties of JAK-inhibitors on macrophages in vitro and in vivo: Perspectives for scleroderma-associated interstitial lung disease

Abstract: Inflammation and Immunopharmacology Conflict of interest: the authors have no conflict of interest to declare. mimics scleroderma-associated ILD. In this model, we showed that ruxolitinib significantly prevented the upregulation of pro-inflammatory M1 markers (TNF, CXCL10, NOS2) and pro-fibrotic M2 markers (Arg1 and Chi3L3). These results were associated with an improvement of skin and pulmonary involvement. Overall, our results suggest that the combined anti-inflammatory and anti-fibrotic properties of JAK2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 67 publications
4
86
0
Order By: Relevance
“…This pathway is dysregulated in obesity and metabolic diseases [ 75 ]. A recent study reported the use of JAK inhibitors on pathologies with lung fibrosis involvement showing that JAK/STAT plays a role in the development of fibrosis [ 76 ]. Moreover, other studies highlight lung fibrotic stability after the administration of JAK inhibitors such as Baricitinib in patients with rheumatoid arthritis and lung involvement [ 77 ].…”
Section: Onset Of Fibrosis: the Contribution Of Dysregulated Lipidmentioning
confidence: 99%
“…This pathway is dysregulated in obesity and metabolic diseases [ 75 ]. A recent study reported the use of JAK inhibitors on pathologies with lung fibrosis involvement showing that JAK/STAT plays a role in the development of fibrosis [ 76 ]. Moreover, other studies highlight lung fibrotic stability after the administration of JAK inhibitors such as Baricitinib in patients with rheumatoid arthritis and lung involvement [ 77 ].…”
Section: Onset Of Fibrosis: the Contribution Of Dysregulated Lipidmentioning
confidence: 99%
“…LPS binds to the TLR4 macrophage membrane receptor, to trigger the differentiation of M1 phenotype macrophages involved in pro-inflammatory responses and the production of pro-inflammatory related factors through the activation of intracellular signaling cascades, including the mitogen-activated protein kinase (MAPK), 8 nuclear factor kappa-B (NF-κB), 6 , 8 Janus kinase (JAK)-signal transducer and activator of transcription (STAT) pathways. 9 Activated macrophages are usually divided into two categories, M1-like and M2-like macrophages. 10 The M1 differentiation of macrophages is enhanced in the early stage of sepsis, probably due to stimulation by cytokines, including interferon-γ (IFN-γ) and granulocyte macrophage colony stimulating factor (GM-CSF), and exogenous bacterial toxins, such as LPS.…”
Section: Introductionmentioning
confidence: 99%
“…Tofacitinib is a “ pan JAK inhibitor” as it has a low JAK selectivity being able to block JAK1, JAK2, and JAK3 [ 31 ]. Some major mediators which are deemed fundamental in SSc pathogenesis are indeed involved in JAK/STAT signalling pathway: IL-6, IFN type 1 and 2 and most importantly IL-4 and IL-13 [ 32 ]. Moreover, different mouse models of SSc showed a potent anti-fibrotic effect for tofacitinib [ 30 ].…”
Section: Resultsmentioning
confidence: 99%